Effects of pulse charging on the performances of lithium-ion batteries. (February 2019) - Li, Shaoqing; Wu, Qiang; Zhang, Dan; Liu, Zhongsheng; He, Yi; Wang, Zhong Lin; Sun, Chunwen
Abstract: Gaining insight into the effects of pulse charging on the performances of energy storage devices is very important for the practical applications of triboelectric nanogenerators (TENGs). In this work, the effects of pulse charging on lithium-ion batteries (LIBs) are investigated. Energy efficiency of the pulse power source coupled with a LIB at different pulse charge voltages is examined. A peak value efficiency of 22.9% is observed at a pulse charging voltage of 8.0 V mode. All-atom classical molecular dynamics simulations suggest that the different diffusion coefficients of Li ion in electrolyte under different applied voltage may be responsible for the different energy efficiencies. Moreover, the cycle performances of the LIBs with intermittent and continuous pulse charging were also investigated. Bad cycling performance of LIBs at pulse charging modes is ascribed to the pulverization of electrode particles arising from the larger strain during cycling, which is corroborated by the software simulation. Based on these results, we further designed a better procedure by combining galvanostatic charge-discharge (GCD) mode with pulse charging mode to improve the battery performance. Graphical abstract: The effects of pulsed charging on performance of LIBs are revealed. The energy efficiencies of the pulse power source with a LIB system are investigated. The bad cycling performance of LIBs at pulse charging modes is ascribed to the pulverization of electrode particles arising from the larger strain during cycling, which is corroborated by the software simulation. Based on these results, we further designed a better procedure by combining galvanostatic charge-discharge (GCD) mode with pulse charging mode to improve the battery performance. Highlights: The effects of pulsed charging on performance of LIBs are revealed. The bad cycling performance of LIBs at pulse charging mode is ascribed to the pulverization of electrode particles. A better procedure combining galvanostatic charge-discharge with pulse charging modes is proposed to improve the battery performance.